2009
DOI: 10.1159/000192082
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Penetration into Rabbit Aqueous Humor Is Comparable between Preserved and Preservative-Free Tafluprost

Abstract: Background: Some studies have shown that benzalkonium chloride (BAK), a preservative used in antiglaucoma medications, can increase corneal permeability by acting as a penetration enhancer. Tafluprost is a new prostaglandin F2α analog in clinical use for the treatment of ocular hypertension and glaucoma. Methods: This study evaluated the corneal penetration of preservative-free tafluprost 0.0015% eye drops and tafluprost 0.0015% eye drops preserved with 0.01% BAK into the aqueous humor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 31 publications
(18 reference statements)
2
23
1
Order By: Relevance
“…It has been suggested that the preservative benzalkonium chloride may be an important factor for drug penetration, and may improve the effectiveness of PC glaucoma drugs [18,19]. However, other data have not supported this hypothesis [20]. Our study showed that both PF and PC dorzolamide/timolol were equally effective in lowering IOP, and there was no evidence that the addition of benzalkonium chloride provided additional efficacy.…”
Section: Discussioncontrasting
confidence: 64%
“…It has been suggested that the preservative benzalkonium chloride may be an important factor for drug penetration, and may improve the effectiveness of PC glaucoma drugs [18,19]. However, other data have not supported this hypothesis [20]. Our study showed that both PF and PC dorzolamide/timolol were equally effective in lowering IOP, and there was no evidence that the addition of benzalkonium chloride provided additional efficacy.…”
Section: Discussioncontrasting
confidence: 64%
“…In vitro experimental systems using cultured cells are often employed to evaluate the barrier function of the corneal epithelium as well as injuries of the corneal epithelium caused by various drugs (Fukuda and Sasaki, 2012: Pellinen and Lokkila, 2009: Yee et al, 2006. These experimental systems provide an excellent means for the objective comparison of the potential for cornea injury among several ophthalmic solutions; however, the extent to which these experimental models reflect the condition of the eyes in vivo remains unclear (Denoyer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the corneal penetration of tafluprost into the aqueous humour of rabbits following a single dose of preservativefree tafluprost 0.0015 % was generally similar to that after a single dose of preservative-containing tafluprost 0.0015 % [15]. Following ocular instillation, timolol is absorbed through the cornea, with its corneal penetration slightly less following a single dose of tafluprost/timolol than following a single dose of timolol alone in rabbits [6].…”
Section: Pharmacokinetic Properties Of Tafluprost/ Timololmentioning
confidence: 99%